(untitled) (UNIHumanitas, 2022)
The present research titled emotional characteristics of adolescents who experience paternal emotional deprivation, year 2022, was developed with the main objective of describing the emotional characteristics of adolescents in the third cycle of schooling, who attend a public school, and experience paternal emotional deprivation. At a methodological level, it was a descriptive study because the object of study was the emotional characteristics of adolescents; non-experimental because it does not have manipulation of variables; quantitative approach, therefore, data collection and analysis were used to answer the research questions; cross-sectional, since the data were taken at one time; the non-probabilistic sample made up of 27 students of both sexes. The Capacities and Difficulties Questionnaire (SDQ) was used as a data collection instrument, which is made up of 5 scales, of which 3 were used. It was applied in person during the safe return to classes protocol due to the COVID pandemic. -19 in 2021. As a result, the research showed that adolescents externalize feelings and moods by 11%, such as: sadness, or the desire to cry. In consideration of this, it is highlighted that these results allow us to investigate the possible factors that may predispose the individual to develop these psychological characteristics.